Answering user queries from hotel ontology for decision making - Hasany, Noman; Selamat, Mohd Hasan (IEEE, 2011)
Semantic web comes out with the vision of making human readable information to be machine processable. Ontology, the core of semantic web, with concept instantiations serves as a domain knowledge base while semantic web query language provides retrieval of that information. In this paper, we presented a system that populates hotel related information in the ontology and a natural language querying platform to retrieve the information from a common interface for decision making. A simple user experiment shows that the system is time effective and helpful in making decisions with minimum queries as compared to browsing even with selected sites.